2017
DOI: 10.5539/elt.v10n12p196
|View full text |Cite
|
Sign up to set email alerts
|

The Acquisition of English Word Stress by Mandarin EFL Learners

Abstract: Compared with the study of acquisition of syntax and morphology, there is a relative lack of research on the acquisition of phonology, the L2 acquisition of word stress in particular. This paper investigates the production of word stress by 70 Chinese college students in their reading aloud. Altogether 350 minutes' recordings were collected and coded. The result shows that improper assignment of word stress most likely occurs in two-syllable words and three-syllable words and on the first syllable. The factors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 13 publications
1
11
0
Order By: Relevance
“…There are several studies conducted by some researchers like Ma and Tan (2013), Liu (2017), Yuan and Cheng (2017) who revealed the influences of mother tongue in learning L2 pronunciation. Another research done by Weda (2012) investigated stress shifts of English utterances made by Indonesian speakers of English.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are several studies conducted by some researchers like Ma and Tan (2013), Liu (2017), Yuan and Cheng (2017) who revealed the influences of mother tongue in learning L2 pronunciation. Another research done by Weda (2012) investigated stress shifts of English utterances made by Indonesian speakers of English.…”
Section: Introductionmentioning
confidence: 99%
“…They examined the most common errors in pronunciation and the reasons for them in order to make recommendations on how to teach and learn English pronunciation. Liu (2017) investigated how 70 Chinese college students produced word stress while reading aloud. The findings revealed that improper word stress assignment occurs most frequently in two-syllable words, three-syllable words, and the first syllable.…”
Section: Introductionmentioning
confidence: 99%
“…Fixed stress pattern means that stress falls on one fixed syllable above every word and its position can be predicted based on the phonological features of the word. Languages such as these do not pose a challenge to cross-linguistic phonological investigations about word-stress behavior and their stress pattern can be easily acquired by foreign language learners (Al-Jarrah, R., 2002; Altmann, H., 2006 8 ; Liu, D., 2017 9 ). Meanwhile, there are some other languages such as Arabic and English that have not fixed stress patterns, they have stress rules that differ from phonological context to another (Al-Jarrah, R., 2002; Liu, D., 2017).…”
mentioning
confidence: 99%
“…It is not just the segment, i.e. the sounds of the L2 (Liu, 2017). Incorrect placement of primary stress in L2 words may lead to the breakdown of communication (Liu, 2017).…”
mentioning
confidence: 99%
“…the sounds of the L2 (Liu, 2017). Incorrect placement of primary stress in L2 words may lead to the breakdown of communication (Liu, 2017). Incorrect placement of primary stress in L2 words may lead to the breakdown of communication (Liu, 2017).…”
mentioning
confidence: 99%